Bioconversion of domestic wastewater sludge by immobilized mixed culture of Penicillum Corylophilum WWZA1003 and Aspergillus Niger SCahmA103 - Alam, Md. Zahangir; Fakhru’l-Razi, Ahmadun; Idris, Azni; Abd-Aziz, Suraini (Taylor and Francis Inc., 2002)
The bioconversion of domestic wastewater sludge by immobilized mixed culture of filamentous fungi was investigated in a laboratory. The potential mixed culture of Penicillium corylophilum WWZA1003 and Aspergillus niger SCahmA103 was isolated from its local habitats (wastewater and sludge cake) and optimized on the basis of biodegradability and dewaterability of treated sludge. The observed results in this study showed that the sludge treatment was highly influenced by the effect of immobilized mixed fungi using liquid state bioconversion (LSB) process. The maximum production of dry filter cake (DFC) was enriched with fungal biomass to about 20.05 g/kg containing 23.47 g/kg of soluble protein after 4 days of fungal treatment. The reduction of COD, TSS, turbidity (optical density against distilled water, 660 nm), reducing sugar and protein in supernatant and filtration rate of treated sludge were influenced by the fungal mixed culture as compared to control (uninnoculated). After these processes, 99.4% of TSS, 98.05% of turbidity,76.2% of soluble protein, 98% of reducing sugar and 92.4% of COD in supernatant of treated sludge were removed. Filtration time was decreased tremendously by the microbial treatment after 2 days of incubation. The effect of fungal strain on pH was also studied and presented. Effective bioconversion was observed after 4 days of fungal treatment.